Gendered Images Of Veil: The Case Of Contemporary Art Practice In Pakistan Proposed - Bano Baloch, Waheeda (2016)
Objective: The aim of this article is to trace how the gender of an artist influences the images that he/she creates in a particular cultural context, and how those images become gendered. Does the cultural constraint or social norms effect a creation depicting the same subjects, when made by man or woman of the same culture and time? Methodology: The work of two contemporary Pakistani male and female artists is used for the analysis, both of these artists have created the images depicting women behind the veil. The analysis is carried out with the help of feminist theory and it goes into the questions like gender, authorship, gaze, artist’s social, political, economic and cultural background of the artists. Analysis: The images of veil are a very popular subject in contemporary Pakistani art, however, veil is a very controversial subject in context with its representation in Islam as well as in the contemporary political scenario of the world. The artists using this sort of cultural and political imagery are promoted by the Western institutions which is another reflection of the politics behind the artistic creation. Many contemporary Pakistani artists including men and women were fascinated to draw ‘women behind the veil’ to represent the oppressed women in Pakistani society in their art. This article traces the politics of gender through the represented images of veil made by Pakistani male and female artists. Therefore, the images by Aisha Khalid (female artist) and Rashid Rana (male artist) are chosen for the analysis, both created the iconic images of veiled women. Khalid uses geometric pattern and only reflects the draperies in her work, on the other hand, Rana uses pornographic imagery to build the bigger picture of the veil which is the point of departure for this paper. Conclusion: Images of veil reflect the gender of their maker and therefore they can also be seen as gendered.